Essays on Iran and Israel an Indian perspective - Cheema, Sujata Ashwarya (KW Publishers Pvt Ltd, 2014)
This book, containing essays on themes relating to India's relations with Iran and Israel, deals with issues that have been intensely debated in the country for some time now. India's robust ties with both Iran and Israel - bitter adversaries for more than three decades - have intrigued West Asia watchers. The essays herein highlight the parallel nature of India's engagements with the two countries and attempt to understand the critical concept of strategic autonomy that defines India's foreign policy postures on contentious issues. The first five essays touch on the central drivers of India's Iran policy and discuss the limits on New Delhi's relations with the Islamic Republic. The last three essays dealing with Israel highlight the significance of India's intervention on questions relating to Israel as well as Israel's inspirational connection with India. With its unique treatment, lucid analysis and unusual organisation, this factually informed and policy oriented collection of essays on India, Iran and Israel will be an extremely useful resource for scholars, students, policymakers and diplomats alike. It will also interest business community involved with the West Asian region as well as any intelligent layperson looking for facts and figures on subjects discussed in the book